Osteomyelitis of maxilla: An unusual case - SriMallika Dasam; Tatapudi Ramesh; Moturi Kishore; Ravikanth Manyam (Wolters Kluwer Medknow Publications, 2020)
Osteomyelitis of facial bones is a common condition. It tends to occur more commonly in the mandible than in the maxilla as the maxilla has collateral blood flow, a thin cortical bone, which makes it less prone to infections. We report an unusual case of maxillary osteomyelitis involving the left half of the maxilla in a 43-year-old, systemically healthy male with a literature review. Intraoral examination revealed exposed denuded bone in the left maxillary region. Radiograph investigations confirmed the diagnosis of osteomyelitis of the left maxilla.